1997
DOI: 10.1002/(sici)1097-0215(19970807)72:4<581::aid-ijc5>3.0.co;2-m
|View full text |Cite
|
Sign up to set email alerts
|

mRNA expression of ligands of the epidermal-growth-factor-receptor in the uterus

Abstract: Six different ligands of the epidermal-growth-factor receptor (EGFR) have been identified in the past. In some cervical squamous-cell carcinomas, an increased amount of proteins binding to the EGFR has been reported. In order to identify the mRNA of EGFR ligands (EGFRL), which might be over-expressed in cervical and endometrial cancers, we performed semi-quantitative reverse-transcription/polymerase chain reactions (RT-PCR) for all 6 EGFRL in RNA extracts of normal and malignant tissue samples of the human ute… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0

Year Published

1998
1998
2015
2015

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 29 publications
(15 citation statements)
references
References 15 publications
0
15
0
Order By: Relevance
“…Earlier clinical studies in other disease entities show that potential markers of sensitivity to EGFR TKIs include the presence of EGFR gene amplification, mutations of the EGFR gene, and increased expression of EGFR ligands (Baselga and Arteaga, 2005). Earlier studies have demonstrated significantly higher expression levels of the EGFR ligands TGF-a and amphiregulin in EC compared with normal endometrium (Pfeiffer et al, 1997;Ejskjaer et al, 2007). The roles of EGFR gene amplification or mutations in EC, however, have not yet been studied.…”
Section: Discussionmentioning
confidence: 99%
“…Earlier clinical studies in other disease entities show that potential markers of sensitivity to EGFR TKIs include the presence of EGFR gene amplification, mutations of the EGFR gene, and increased expression of EGFR ligands (Baselga and Arteaga, 2005). Earlier studies have demonstrated significantly higher expression levels of the EGFR ligands TGF-a and amphiregulin in EC compared with normal endometrium (Pfeiffer et al, 1997;Ejskjaer et al, 2007). The roles of EGFR gene amplification or mutations in EC, however, have not yet been studied.…”
Section: Discussionmentioning
confidence: 99%
“…The linearity of the amplifications was controlled by densitometric scanning of the gels and plotting of the density against the cycle number. The amplifications were analysed in the linear range as described in detail previously [41]. Shortened standard fragments of these sequences were generated by deleting 50 to 80 bp of internal sequence.…”
Section: Methodsmentioning
confidence: 99%
“…Showing conservation with the mouse, HB-EGF peaks at the window of implantation (Yoo et al 1997) and ErbB4 is expressed in the trophectoderm in periimplantation human blastocysts (Chobotova et al 2002). In addition, correlative links between elevated expression of Ar and TGF-a with endometrial cancers have been made (Pfeiffer et al 1997).…”
Section: Growth Factorsmentioning
confidence: 99%